2016
DOI: 10.1371/journal.pone.0156243
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Is a Strong Risk Factor for Minor Ischemic Stroke and Subsequent Vascular Events

Abstract: BackgroundMinor ischemic stroke (MIS) represents a major global public health problem worldwide due to high incidence. The aim of this study was to investigate whether metabolic syndrome (MetS) is a strong risk for MIS and subsequent vascular events (SVE).MethodsA retrospective cohort study was performed examining symptomatic MIS in a Chinese neurologic outpatient population aged over 25 years without history of stroke. MetS was defined using the International Diabetes Federation criteria. MIS was diagnosed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Our study also demonstrated that diabetes associates with NKP compared with non-NKP, but not when compared with the no-KP group. Although we did not differentiate type 1 and type 2 diabetes, it is plausible that the metabolic syndrome underlies the onset and progression of neuropathy and obesity, and its consequences are potential driving adverse factors that propagate altered nerve functioning and injury [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also demonstrated that diabetes associates with NKP compared with non-NKP, but not when compared with the no-KP group. Although we did not differentiate type 1 and type 2 diabetes, it is plausible that the metabolic syndrome underlies the onset and progression of neuropathy and obesity, and its consequences are potential driving adverse factors that propagate altered nerve functioning and injury [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…72 A retrospective study of 1,361 outpatients with minor stroke showed that individuals with metabolic syndrome had more frequent subsequent vascular events than those without metabolic syndrome. 73 On the other hand, a prospective study of 1,087 individuals with mild-tomoderate ischemic stroke, followed for 5 years, showed that the risk of recurrent stroke in the absence of diabetes was similar to those without metabolic syndrome or diabetes. 74 The primary goal of clinical management of metabolic syndrome is to reduce the atherogenic risk factors.…”
Section: Metabolic Syndrome and Strokementioning
confidence: 99%
“…1,2 The importance of recognizing this syndrome lies in the fact that it is a risk factor for type 2 diabetes mellitus, coronary artery disease, stroke, and cancers and all-cause mortality. [3][4][5][6][7][8][9] The criteria for diagnosing MS have been proposed by various relevant authorities. [10][11][12][13][14] These criteria have both contrasting and similar features [ Table 1].…”
Section: Introductionmentioning
confidence: 99%